Investigation of metabolites produced by rice blast fungus, Magnaporthe oryzae during appressorium development - Md Zain, Azian (2020)
Magnaporthe oryzae is important fungal pathogen that caused serious rice blast disease worldwide. The disease cycle of M. oryzae is unique, required appressorium in order to penetrate the host cells. Appressorium is critical structure to cause disease but metabolites produced during appressorium development is poorly understood. To date, there is limited information on fungal metabolites and their functions produced by M. oryzae during appressoria development. Therefore, the aim of this study was to determine metabolites produced by M. oryzae during appressorium development in vitro and revealed important metabolic pathways involved. Untargeted metabolomics of Proton Nuclear Magnetic Resonance (1H NMR) was used to determine metabolites from M. oryzae extracts and any metabolite changes was observed during 0 h, 8 h and 24 h development stage. Spectra of 1H NMR were analyzed using multivariate data analysis (MVDA) and model validation was studied. Rich numbers of primary metabolites were detected from 1H NMR spectra and there were 43 metabolites identified putatively based on metabolomics library and previous reports. Partial least square discriminant analysis (PLS-DA) disclosed metabolites pattern among 0 h, 8 h, 24 h and mycelia. Metabolites that showed significant changes (p < 0.05) among groups of 0 h, 8 h, 24 h and mycelia including butyrate, leucine, isoleucine, valine, isobutyrate, ethanol, methylmalonate, threonine, lactate, alanine, lysine, arginine, 4-aminobutyrate, glutamate, homoserine, isocitrate, glutamine, choline, glucose, xylose, mannose, glycerol, mannitol, glucitol, tyrosine, sucrose and tryptophan. Orthogonal projections to latent structures discriminant analysis (OPLS-DA) revealed metabolites produced during each time-point of 0 h, 8 h, 24 h. Number of metabolites at 8 h and 24 h were produced the highest compared to 0 h. Then, metabolomics pathway analysis (MetPa 4.0) from Metaboanalyst.ca was used to illustrate metabolic pathways involved during appressorium development. There were eight key metabolic pathways that highly involved during appressorium development including amino acids, carbohydrates and lipid metabolisms. Fungal metabolites produced by M. oryzae have potential for targeted metabolomics to target specific metabolite or pathways required for pathogenicity thus provide opportunity in developing inhibitors for rice blast disease.